Program of Prenatal Sensorial Stimulation - Leiva de Chamochumbi, Martha (2004)
The Program of Prenatal Sensorial Stimulation, it was created with the apparent necessity of to look for that our pregnant Peruvian achieve a vividly significant accommodation process toward the formation of their babies and to offer them the possibility to maintain a harmonic balance among the; controlling their stress previous orientation and treatment to their difficulties; and this way to also be able to potential from the uterus the abilities of maturation of the fetus in formation. The concept of the baby´s development is respect, of the couple and of the family.